Respect and Take Care of Things = Apni Cheezon Ki Qadar Karein - Meiners, Cheri J.; Illustrated by Johnson, Meredith (Karachi Oxford University Press, 2016)
Everything has a place. Things last longer when we take care of them. Respect, responsibility, and stewardship are concepts that even young children can relate to$1 (Bbecause they have things they value. This book encourages children to pick up after themselves, put things back where they belong, and ask permission to use things that don$1 (Bt belong to them. It also teaches simple environmental awareness: respecting and taking care of the earth. Includes ideas for adult-led activities and discussions.s
Include Illustrations.
These books will help young children learn and practice basic social and emotional skills through real life situations and examples. Attractively illustrated, the stories are useful for teaching children in pre-primary and primary classes to behave responsibly and respectfully towards everyone. Each book includes a section for adults with discussion questions, games, activities, and tips that reinforce the skills and ideas being taught.
Keywords: Respect -- Caring -- Responsibility